Laura E. Rodríguez Dulanto: The first clinical trial performed by a female physician in Peru.: Laura E. Rodriguez Dulanto: El primer experimento clínico realizado por una médica graduada en el Perú. - Salaverry García , Oswaldo (2024)
Laura Gutiérrez Dulanto has been highlighted for her status as the first woman to graduate in Medicine in Peru. Her high intellectual qualities have been noted from various perspectives, as well as her effort and tenacity to overcome the difficulties of pursuing university studies, particularly in scientific disciplines, then reserved exclusively for men. It has been pointed out, however, that due to the limitations imposed on women at the time, she had a diminished professional activity and little scientific production, which has not been reviewed by existing historiography. This article analyzes his scientific production, especially a clinical study developed in a women's hospital in Lima, Peru, showing his ideas about science and medicine and identifying a clear, modern and innovative thought, not exempt from social sensitivity, in addition. to show herself as a keen and thorough observer of clinical-surgical problems.